High rate of non-treatment among osteoporotic women enrolled in a US Medicare plan. (1st November 2016) - Yang, Xiaoqin; Sajjan, Shiva; Modi, Ankita
Abstract: Objective: To estimate the rate of non-treatment among elderly women with osteoporosis (OP) and to examine the association between patient characteristics and receiving treatment. Research design and methods: This cross-sectional, retrospective, observational study utilized patient information and claims from the Humana database to identify Medicare covered women aged ≥65 years old and continuously enrolled with evidence of either an OP diagnosis or an OP-related fracture during 2007–2011. The main outcome was receipt of pharmacological treatment of OP during 2012 (follow-up). The percentage of non-treatment was calculated and a stepwise selection logistic regression model was employed to estimate the association between baseline demographic and clinical characteristics and receiving treatment. Results: A total of 109, 829 patients were included. Mean age was 75.7 years and 79.4% were identified with OP through OP diagnosis codes and did not have evidence of a prior fracture. Approximately one-third (32%) of patients had used OP medications during the baseline period, and 39% had experienced at least one gastro-intestinal event during baseline. Among all patients, 71.4% did not receive OP therapy during follow-up. The strongest factor associated with receiving treatment was prior use of OP therapy (odds ratio [OR] = 31.3; p  < .001). Among the subgroup of patients with baseline fractures, 75.9% did not receive OP therapy during follow-up and the strongest factor associated with receiving treatment remained prior use of OP therapy (OR = 20.4; p  < .001). Those with high comorbidity burden were less likely to receive treatment in both the overall cohort and within the subgroup with baseline fractures. Conclusions: Among Medicare-eligible women aged ≥65 identified with OP between 2007 and 2011, 71.4% did not receive OP treatment during 2012, including 75.9% of the subgroup of patients with a prior fracture. The use of diagnosis and procedures codes to identify patients with osteoporosis is subject to variation in coding.